Non-invasive positive pressure ventilation immediately after extubation in children - a randomized study - Anil Sachdev; Sameer Punia; Dhiren Gupta; Neeraj Gupta; Suresh Gupta (Wolters Kluwer Medknow Publications, 2019)
Objective: To compare the effects of noninvasive positive pressure ventilation(NIPPV) and oxygen (OX) therapy in post-extubated patients on re-intubation rate, length of PICU and hospital stay and mortality. Methods: It was randomized interventional study.All patients on mechanical ventilation (MV) for more than 48 hours were assessed and were enrolled only after fulfilling inclusion criteria. Patients were randomized prior to extubation to receive NIPPV or OX therapy with mask after planned weaning and extubation following institutional protocols. Reintubation required within 48 hours of extubation was considered extubation failure. Results: 97 out of 137 patients were randomized and analyzed. There was no significant difference between two groups in the distribution of underlying disease, PRISM score 12 and 24, arterial blood gases, hemodynamic parameters and duration of invasive MV prior to extubation.The PaO2 at 2 and 6 hours after extubation were significantly higher in patients receiving NIPPV (P value 0.04, 0.01 respectively). Nineteen (19.5%) patients were reintubated within 48 hours of extubation. Thirteen (25%) patients belonged to OX group and 6 (13%) were in NIPPV group (P value 0.12, odds ratio 2.28, 95% CI 0.78-6.61). Commonest reason for reintubation was increased work of breathing. Four patients with failed extubation from OX group were provided rescue NIPPV with success. The total duration of stay in the PICU and hospital were not significantly different in study groups (P value 0.4, 0.4 respectively). Conclusion: Although reintubation were less, our study did not support early elective use of NIPPV immediately after extubation in children.